Indigenous Peoples in Nepal’s Forestry Sector Public Discourses - Rai, Jailab Kumar (Tribhuvan University Journal, 2020)
This paper attempts to unfold Nepal’s forestry sector discourses from the perspectives of the presence and contribution of indigenous peoples in forestry sector public discourses. The paper deals with five dimensions of indigenous peoples as part of public discourses. They include: (a) policies and legislations;(b) physical presence in the forestry sector government institutions; (c) number of publications; (d) number of authors; and (e) presence in the public events. The qualitative information, derived from the participation and observation of the public events, is complemented by quantitative information compiled from the relevant reports and publications. I found that participation and contribution of indigenous peoples in Nepal’s forestry sectors pubic discourses is relatively less. I argue that inadequacy of Nepal’s forestry sector policies and practices is a replication of the overall situation of Nepali society that has fostered the exclusion of indigenous peoples.